Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1158/1541-7786.mcr-09-0326
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Zinc Finger 1 Induces Migration, Invasion, and In vivo Metastasis through Axl Gene Expression in Solid Cancer

Abstract: Myeloid zinc finger 1 (MZF1) is a member of the SCAN domain family transcription factors that form dimers through their highly conserved SCAN motifs. Silencing of MZF1 inhibits cell proliferation, and abnormal expression of MZF1 results in cancer development. However, a potential role of MZF1 in metastasis remains unclear. Axl is a receptor tyrosine kinase and was first identified as a transforming gene in chronic myeloid leukemia. Axl overexpression induces proliferation, migration, and invasion and is highly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 46 publications
5
129
0
Order By: Relevance
“…Axl-mRNA and Axl protein expression significantly inversely correlated with the miR-34a expression, and cell invading capacity positively correlated with Axl protein amounts and inversely with miR-34a expression. In general, our findings strongly support the existing literature that Axl is an oncogene and miR-34a is a tumor suppressor (Hafizi and Dahlback, 2006;Vajkoczy et al, 2006;Bommer et al, 2007;Welch et al, 2007;Mudduluru et al, 2010). Previous studies reported that miR-34a can inhibit cell cycle (CCNE2, CDK4, CDK6, Cyclin E2 and E2F5), anti-apoptotic protein (BCL2) and invasion (MET) inducing genes (Bommer et al, 2007;Chang et al, 2007;He et al, 2007;Raver-Shapira et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Axl-mRNA and Axl protein expression significantly inversely correlated with the miR-34a expression, and cell invading capacity positively correlated with Axl protein amounts and inversely with miR-34a expression. In general, our findings strongly support the existing literature that Axl is an oncogene and miR-34a is a tumor suppressor (Hafizi and Dahlback, 2006;Vajkoczy et al, 2006;Bommer et al, 2007;Welch et al, 2007;Mudduluru et al, 2010). Previous studies reported that miR-34a can inhibit cell cycle (CCNE2, CDK4, CDK6, Cyclin E2 and E2F5), anti-apoptotic protein (BCL2) and invasion (MET) inducing genes (Bommer et al, 2007;Chang et al, 2007;He et al, 2007;Raver-Shapira et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…miR-34a is a p53 target gene that presumably mediates induction of apoptosis, cell cycle arrest and senescence by p53. Subsequently, Axl is known to induce migration, invasion and distant metastasis (Vajkoczy et al, 2006;Mudduluru et al, 2010). We now demonstrate that miR-34a and miR199a are potent inhibitors of migration, invasion (H1299, MDA-MB-231 and Rko) and tumor growth and, in vivo distant metastasis by CAM assay (H1299 and Rko).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations